The Effect of Governance on Firm Value with Financial Performance as a Mediation Variable in Go Public Companies in Indonesia - Kurniati W. Andani; Yusbardini Yusbardini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze corporate governance on firm value with financial performance as a mediating variable in manufacturing companies on the Indonesia Stock Exchange (IDX) with corporate governance indicators consisting of CEO Duality and CEO Tenure. The benefit of this research is that good governance will increase financial performance and firm value. The sample used in this study consisted of the annual financial statements of all companies listed on the Indonesia Stock Exchange. The sample of this study was 44 companies selected through purposive sampling method. The company data for this sample selection was taken from financial reports and annual reports from the official website of the Indonesia Stock Exchange, namely idx.co.id and the company's official website. Data processing is done using Eviews. The results of this study can show the effect of CEO Duality and CEO Tenure on firm value and financial performance as mediating variables. The results show that CEO Duality, CEO Tenure has an effect on, financial performance and, CEO Duality, CEO Tenure has an effect on firm value, financial performance is able to mediate, CEO Duality and firm Value and financial performance is not able to mediate CEO Tenure and Firm Value.